Letter (copy) : Clothes for Spain - Tewson, Vincent
028-0088-001 HVT/FC/433. Secretary's. 21st January, 1937. Mr. A. Conley, 20, Park Place, LEEDS. Dear Mr. Conley, Clothes for Spain. I am sorry for the delay in sending the cheque, but when you spoke to me yesterday I was in a meeting and was unable to get a letter off last night. I am, however, enclosing a cheque for £100 and should like to say how greatly we appreciate the effort you are making. I hope you will be very successful. With best wishes, Yours sincerely, Assistant Secretary. P.S. I shall be glad to receive your receipt for £100 at your convenience. Cheque. 292/946/28/88